2017
DOI: 10.1002/phar.1938
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Biomarkers of Disease Activity and Therapeutic Response after Initiating Methotrexate Therapy in Patients with Juvenile Idiopathic Arthritis

Abstract: Plasma cytokine levels were responsive to MTX therapy in patients with JIA, but only TNF-α and IL-6 levels were consistently associated with disease activity and therapeutic response. Increased TNF-α levels at baseline were associated with failure to respond to standard-dose MTX and the need for more aggressive drug therapy. Initiation of ETN resulted in increased TNF-α levels that corresponded with therapeutic response, suggesting a potential clinical benefit of monitoring TNF-α levels as a pharmacodynamic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
2
9
0
2
Order By: Relevance
“…In studies examining the association between methotrexate disposition and its actions (both desirable and adverse) in pediatric patients with juvenile idiopathic arthritis, Becker et al have examined both the intracellular concentrations of methotrexate polyglutamates and the impact of genotype on methotrexate polyglutamate variability . More recently, they have demonstrated that, in pediatric patients with juvenile idiopathic arthritis, plasma cytokine levels (tumor necrosis factor‐α and interleukin‐6) appeared to have a predictive association as a PD biomarker of etanercept activity …”
Section: Developmental Changes In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies examining the association between methotrexate disposition and its actions (both desirable and adverse) in pediatric patients with juvenile idiopathic arthritis, Becker et al have examined both the intracellular concentrations of methotrexate polyglutamates and the impact of genotype on methotrexate polyglutamate variability . More recently, they have demonstrated that, in pediatric patients with juvenile idiopathic arthritis, plasma cytokine levels (tumor necrosis factor‐α and interleukin‐6) appeared to have a predictive association as a PD biomarker of etanercept activity …”
Section: Developmental Changes In Pdmentioning
confidence: 99%
“…116 More recently, they have demonstrated that, in pediatric patients with juvenile idiopathic arthritis, plasma cytokine levels (tumor necrosis factor-α and interleukin-6) appeared to have a predictive association as a PD biomarker of etanercept activity. 117 With the resurgence of methicillin-resistant Staphylococcus aureus in the community, the antimicrobial combination product, trimethoprim-sulfamethoxazole (TMP-SMX) has become more widely used in pediatric practice. This medication has been linked to hypersensitivity reactions including 2 that are potentially lifethreatening: Stevens Johnson syndrome and toxic epidermal necrolysis.…”
Section: S21mentioning
confidence: 99%
“…These studies have been based on the recognition that cytokines represent mediators of disease activity in JIA, are responsive to drug therapy, and are the target of newer therapies. Most notably, recent work by our group has found that patients with elevated plasma TNF‐α levels at the time of MTX initiation are more likely to fail MTX therapy and require the addition of a TNFi in the first 3 months of treatment . These finding suggest that disease activity associated with marked elevations in TNF‐α, may benefit from the early addition of TNFi therapy.…”
Section: Pharmacokinetic and Pharmacodynamic Variation And Drug Responsementioning
confidence: 93%
“…Most notably, recent work by our group has found that patients with elevated plasma TNF-α levels at the time of MTX initiation are more likely to fail MTX therapy and require the addition of a TNFi in the first 3 months of treatment. 9 These finding suggest that disease activity associated with marked elevations in TNF-α, may benefit from the early addition of TNFi therapy. Similarly, we have found that elevations in plasma levels of the adipocytokine and rate-limiting enzyme in NAD biosynthesis, nicotinamide phosphoribosyltransferase (NAMPT), is associated with poor response to MTX.…”
Section: Reverse Translation In Advancing Pharmacotherapy In Pediatrimentioning
confidence: 97%
“…We designed a custom panel of cytokines related to disease pathophysiology, 15–19 or based on existing evidence of involvement in response to MTX therapy. 20–25 This panel included interferon gamma (IFNᵧ), granulocyte-macrophage colony-stimulating factor (GM-CSF), TNFɑ, interleukin (IL) 9, IL-10, IL-17A, IL-17F, chemokine C-C motif ligand 20 (CCL20), IL-23, IL-22, IL-33 and ular endothelial growth factor (VEGF). Online supplementary table 1 shows the minimal detectable concentration (MDC) of our assay per cytokine and which bead was used for the detection.…”
Section: Methodsmentioning
confidence: 99%